Development of E-LKPD Based on Realistic Mathematics Education on Three-Variable Linear Equation System Material Oriented to Critical Thinking Skills and Self-Efficacy of Vocational School Students - Khaeriyah Anwar; Kana Hidayati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to (1) describe the characteristics of e-LKPD based on realistic mathematics education on system of linear equations with three variables oriented towards critical thinking skills and self-efficacy of vocational school students, (2) describe the feasibility of e-LKPD based on realistic mathematics education on system of linear equations with three variables oriented towards critical thinking skills and self-efficacy of vocational school students in terms of validity, practicality and effectiveness. This type of research is research and development (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 34 students of class X TKP SMKN 2 Tarakan. In this research, One Group Pretest - Posttest Design was used. The research instruments used were validation sheets, practicality assessment sheets by teachers and students, learning implementation observation sheets, critical thinking ability tests and self-efficacy questionnaires. The results of the research show: (1) the e-LKPD developed contains characteristics found in the RME approach to the material of on system of linear equations with three variables oriented towards critical thinking skills and self-efficacy. The characteristics contained in RME-based e-LKPD include integrated learning, use of context, mathematization and construction processes and interactivity. (2) the RME-based e-LKPD developed meets the criteria for feasibility in terms of validity aspects with a percentage of feasibility according to material experts of 93.4% and media experts of 98.9% with the validation result criteria being very feasible; practicality with a very practical category based on the results of student and teacher responses; effectiveness based on critical thinking skills with classical completeness of students reaching 82.4%, the results of the T-test paired samples-test with a significance level of 5% obtained that there was an influence on students' critical thinking skills after treatment using RME-based e-LKPD, the N-Gain result was 0.73 with a high category, and the effectiveness of e-LKPD on self-efficacy with an increase in each self-efficacy indicator, the N-Gain result was 0.3 in the moderate category, and the results of the Wilcoxon test on self-efficacy data with a significance level of 5%, it was obtained that there was an influence on students' self-efficacy after treatment using RME-based e-LKPD.